2008
DOI: 10.1007/s11064-008-9710-0
|View full text |Cite
|
Sign up to set email alerts
|

The Wnt Antagonist, Dickkopf-1, as a Target for the Treatment of Neurodegenerative Disorders

Abstract: The canonical Wnt pathway contributes to the regulation of neuronal survival and homeostasis in the CNS. Recent evidence suggests that an increased expression of Dickkopf-1 (Dkk-1), a secreted protein that negatively modulates the canonical Wnt pathway, is causally related to processes of neurodegeneration in a number of CNS disorders, including Alzheimer's disease (AD), brain ischemia and temporal lobe epilepsy (TLE). Dkk-1 induction precedes neuronal death in cellular and animal models of excitotoxicity, bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 56 publications
3
40
0
Order By: Relevance
“…[46][47][48] Our results are in accord with the increasingly accepted role for Wnts in the modulation of fundamental aspects of the homeostasis and neuronal function of the adult CNS. 14,17,18,[49][50][51][52][53] In this line of thought, we provide supporting evidences of previous reports describing the expression of most Wnt ligands and receptors by PCR 39 and in situ hybridization analysis, 35 as well as a constitutive active b-catenin-mediated transcription in the dorsal horns and the central canal of the adult spinal cord of mice. 22,32 Interestingly, Wnt3a and Wnt5a have been recently described to be expressed by neurons of the ventral and dorsal horn of adult mice, and that the latter received Wnt3a and Wnt5a synapsis from dorsal root ganglia sensory neurons, with at least involvement of the b-catenin pathway, as evidenced by its enrichment in the pre-and postsynaptic contacts.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…[46][47][48] Our results are in accord with the increasingly accepted role for Wnts in the modulation of fundamental aspects of the homeostasis and neuronal function of the adult CNS. 14,17,18,[49][50][51][52][53] In this line of thought, we provide supporting evidences of previous reports describing the expression of most Wnt ligands and receptors by PCR 39 and in situ hybridization analysis, 35 as well as a constitutive active b-catenin-mediated transcription in the dorsal horns and the central canal of the adult spinal cord of mice. 22,32 Interestingly, Wnt3a and Wnt5a have been recently described to be expressed by neurons of the ventral and dorsal horn of adult mice, and that the latter received Wnt3a and Wnt5a synapsis from dorsal root ganglia sensory neurons, with at least involvement of the b-catenin pathway, as evidenced by its enrichment in the pre-and postsynaptic contacts.…”
Section: Discussionsupporting
confidence: 90%
“…A growing body of evidence suggests that Wnt signaling may be involved in homeostasis and disease progression in adult tissues, [17][18][19][20][21][22][23][24][25][26] including the spinal cord.…”
mentioning
confidence: 99%
“…10,46 Acyl modification of Wnt proteins was also shown to have a crucial role for proteins exiting from the endoplasmic reticulum, secreting to the extracellular domain or binding to the receptor. 21,22 Thus a regulatory mechanism of protein acylation may be necessary for cells to control Wnt/β-catenin signaling activity.…”
Section: Discussionmentioning
confidence: 99%
“…2 Although currently there are no data regarding Ryk functions in oligodendroglial cell death, it should be noted that several reports have shown that, after a CNS injury, the Wnt family of proteins is able to modulate cell survival in other neural cell types, such as neurons. 6,20 Finally, an interesting point of discussion derives from the presence of fibronectin + cells in the lesion epicenter. Several reports have demonstrated the presence of fibronectin in the injury core, even in non-penetrating injuries where meningeal fibroblast invasion and proliferation are minimal.…”
Section: Fig 7 Ryk Is Expressed In Fibronectinmentioning
confidence: 99%
“…[3][4][5] A growing body of evidence suggests that Wnt signalling may be involved in homeostasis and disease progression in adult tissues, [6][7][8][9][10][11] including the spinal cord. 10,[12][13][14][15][16] Consistent with these findings, we have previously shown that most of Wnt ligands and inhibitors are expressed in the adult spinal cord of rats and, following SCI, are differentially induced with at least Wnt/b-catenin signalling activation in cells that appear to be involved in glial scarring.…”
mentioning
confidence: 99%